2015
DOI: 10.1186/s13584-015-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

Solving the worldwide emergency department crowding problem – what can we learn from an Israeli ED?

Abstract: ED crowding is a prevalent and important issue facing hospitals in Israel and around the world, including North and South America, Europe, Australia, Asia and Africa. ED crowding is associated with poorer quality of care and poorer health outcomes, along with extended waits for care. Crowding is caused by a periodic mismatch between the supply of ED and hospital resources and the demand for patient care. In a recent article in the Israel Journal of Health Policy Research, Bashkin et al. present an Ishikawa dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Alameda and Suárez [8] report outliers admission times were 22% longer and in a systematic review undertaken by Metcalfe, et al., [20] found the percentage of Medical Emergency Calls were increased among outlying patients [8,20]. Todate research has iluminated the magnitude of access block and crowding, the intricacies of solutions employed to resolve access block and the resulting impact on patients [3,7,21]. Up until now, evidence remains unreported on the experience of nurse managers responsible for managing resources at times of access block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alameda and Suárez [8] report outliers admission times were 22% longer and in a systematic review undertaken by Metcalfe, et al., [20] found the percentage of Medical Emergency Calls were increased among outlying patients [8,20]. Todate research has iluminated the magnitude of access block and crowding, the intricacies of solutions employed to resolve access block and the resulting impact on patients [3,7,21]. Up until now, evidence remains unreported on the experience of nurse managers responsible for managing resources at times of access block.…”
Section: Discussionmentioning
confidence: 99%
“…Solutions are designed to ensure optimal use of available resources whilst not compromising patient safety [7]. An example being, that when there are no beds available in the patient's specialty ward patients are admitted to another ward bed which may not ordinarily provide the expert care required, as an outlier or border [8,9], or implementing an over-census protocol, a decision typically made by experienced senior nurses to open surge beds [10].…”
Section: Page 3/12mentioning
confidence: 99%
“…A not negligible consequence of these prolonged increments of activity is the lowering of ED services quality and patient safety. In this sense, it has been demonstrated that ED crowding can be associated with poorer quality of care and poorer health outcomes, along with extended waits for care [17] . Similar findings are consistent with those found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding hospitalisation, on the other hand, has many advantages: most importantly, patients will most likely prefer this. With an ever increasing number of presentations, crowding is a long known problem for urban EDs in Switzerland [95] and worldwide [96,97]. Crowding is the result of a mismatch between ED capacity and the number of patients presenting in a given period of time [98].…”
Section: Advances Due To Symptom-oriented Research At Dispositionmentioning
confidence: 99%